Radiation effect studies on partially crystalline bulk amorphous Fe-based metallic glass. Issue 3 (3rd April 2022) - Uslu Kiçeci, Pelin; Akdeniz, M. Vedat; Demirköz, M. Bilge; Mekhrabov, Amdulla
Abstract : The selection of appropriate materials for radiation environments is critical due to the harsh and aggressive conditions found in such environments, which are liable to degrade material properties. Therefore, durability of materials should be tested before being deployed. In this respect, proton tests are required for the materials to be used in the space environment because dominant galactic cosmic rays mostly comprised high energy protons. Bulk metallic glasses are candidate for space environment due to their desirable properties such as high strength, high corrosion resistance, and lack of grain boundaries. In this present study, we report the effect of a 30 MeV proton beam irradiation on the structural, thermal, mechanical, and magnetic properties of partially crystalline bulk amorphous Fe-based metallic glass. Defect size increment in positron annihilation lifetime spectroscopy and small intensity changes on the X-ray diffraction peaks of samples were observed after the irradiation that can be attributed to increasing free volumes. In addition, changes in crystallisation and glass transition temperatures were examined in differential scanning calorimetry. Furthermore, rise in coercivity which is a magnetic property was observed in vibrating sample magnetometer that may associate with the defect size increment. On the other hand, any changes were not observed on the microhardness measurements.